The mystery in Alligator Alley - Marsh, Carole (Peachtree City, GA : Gallopade International/ Carole Marsh Books, 2013)
While Mimi is recovering from a broken leg, Avery and Evan visit the Savannah National Wildlife Refuge with Christina, but they become concerned when they overhear rumors of 'gator poaching,' and become determined to help find the culprits.
"Includes STEM facts & activities"--Back cover.
3.8
3-6
Keywords: Families -- Juvenile fiction; Alligators -- Juvenile fiction; Poaching -- Juvenile fiction; Savannah National Wildlife Refuge (Ga. and S.C.) -- Juvenile fiction; Family life -- Fiction; Alligators -- Fiction; Poaching -- Fiction; Savannah National Wildlife Refuge (Ga. and S.C.) -- Fiction; Mystery and detective stories; Family life -- Fiction; Alligators -- Fiction; Poachers -- Fiction; Trapping -- Fiction; Savannah National Wildlife Refuge (Ga. and S.C.) -- Fiction; Mystery fiction; Mystery fiction